Understanding Indigenous knowledge of conservation and stewardship before implementing co-production with Western methodologies in resource management - Stafford Maracle; Jennifer Maracle; Stephen Lougheed (Journal of Agriculture, Food Systems, and Community Development)
In the face of an increasing global human population and multiple anthropogenic environmental stressors including climate change, the limitations of relying solely on Western science and approaches to mitigating impacts, conserving biodiversity, and managing resources sustainably is apparent. Many Indigenous Peoples have lived sustainably as part of their respective environments for millennia, passing conservation and management practices down generations despite colonization and genocide. Long-standing Indigenous knowledge and philosophies offer alternate worldviews that can complement Western conservation and resource management and may strengthen efforts to restore environmental integrity and conserve species and ecosystems. Researchers often tout the co-production of knowledge with Indigenous collaborators using frameworks like the Kaswentha (Two Row Wampum—Haudenosaunee) and the Etuaptmumk (Two Eyed Seeing—Mi’kmaw) without first seeking to understand the foundations of Indigenous knowledge itself, and its deep roots in environmental sustainability. We develop a thesis of the embedded relational nature of Indigenous knowledges and the unique strengths and perspectives that must be understood before effective and ethical co-production can be possible. We contend that Indigenous knowledge must be treated as a distinct framework to inform conservation and stewardship of biodiversity and nature, rather than selectively integrating it into Western science. Building relationships with local Indigenous nations will help actualize sustainable practices that are rooted in millennia of empirical data. This will help to promote a shift toward a holistic and relational worldview for more impactful conservation action.